Design and application of a mobile nursing trolley (一种新型一体化移动护理推车的设计与应用) - RAN Maomei (冉茂梅); GUO Xue (郭雪); TANG Xuxia (唐绪霞); CHEN Xia (陈夏) (Association of Integrative Nursing, 2023)
Improvement of medical equipment's' function may contribute to the efficiency of nursing care in the general hospital. This paper introduced the design and application of a mobile nursing trolley, which consisted of a mobile computer and a medical trolley. The mobile nursing trolley has been designed to enable nurses to search patient's information and provide nursing service more efficiently. (大型综合医院住院患者多, 护理工作量大, 通过改进相关设施, 有助于提升护理工作效率。本文介绍一种新型一体化移动护理推车, 由移动电脑一体机、护理治疗推车两大部分组成, 便于护理人员及时查询患者资料和提供护理服务。)